Effect of feedstock, impurities, and rancidity on likelihood of spontaneous combustion of oil and biodiesel. Issue 7 (9th August 2022) - Hanson, Brian; Shrestha, Dev S.; Dunkel, Chad
Abstract: Spontaneous combustion of biodiesel has been attributed to the destruction of multiple biodiesel production facilities. This paper investigates common conditions that affect the biodiesel and feedstock oil's propensity for spontaneous combustion. The objective of this research was to develop a short-term test to determine the likelihood of developing spontaneous combustion in a long term. This study used a completely randomized block design which consisted of four main factors; two feedstocks (linseed oil and waste vegetable oil); two fuel types (raw oil and biodiesel); with or without impurity (sodium methylate, a catalyst used in biodiesel production, was used as an impurity); and two levels of rancidity (fresh and rancid fuel) with a total of 16 combinations. The tests prove all four factors play a significant role in affecting the likelihood of spontaneous combustion. A mathematical quantification was deemed necessary to identify the propensity of spontaneous combustion. A Spontaneous Combustion Severity Index (SCSI), a unitless number, was formulated, based on temperature rise normalized by experiment temperature, which correlates with heat generation patterns inside the reactors from 24-h experiments. Spontaneous combustion of biodiesel was observed under accelerated conditions using a fuel mixture with a SCSI number over 0.015.